PENERJEMAHAN ARAB-JAWA TRADISI PESANTREN PADA KARYA KITAB-KITAB KLASIK: ANALISIS FUNGSI - Moh. Masrukhi (Unit Penelitian dan Publikasi Fakultas Ilmu Budaya Universitas Gadjah Mada, 2017)
The aims of education in Javanese pesantren is generally to transmit the teachings of Islam. Its teaching system to this day still refers to the Arabic classic books al-kutubul-mu`tabara (KKbA). In order for KKbA to be understood by the general public, there is an effort to translate it into Javanese language by translating the pesantren model or tradition (PTP). The typical translation of Pesantren is done per word according to the order in the source language (BSu) or the Arabic language. The apparent feature of the translation results is the addition of markers to the grammatical unit functions of the source language in the target language (BSa), like Javanese language. The theory used in this research is the Arabic syntax theory which is already well known and written by Arabic linguists. The result of the research about the marker of the grammatical unit function in KKbA is divided into four parts. This division is done to show the uniqueness of the structure owned by Arabic language. The division includes: a) marker of mubtada ' and khabar function; b) the marker of the functions of fā'il and nāib fā'il, c) the syntactic function marker of maf'ūl bih; and d) the marker of an explanatory function, such as maf'ūl fīh, maf'ūl mutlaq, maf'ūl li ajlihi, hāl, and tamyīz. Thus, this tradition of interpretation of Pesantren in addition to acquiring knowledge of KKbA studied, as well as get knowledge about Arabic grammar.